SUCCESSFULLY DELAYED DELIVERY OF SECOND TWIN AFTER EARLY SECOND TRIMESTER RUPTURE OF MEMBRANES OF THE FIRST TWIN: A CASE REPORT - Jadranka Georgievska; Igor Samardjiski; Ana Daneva Markova; Goran Kocoski (Институт за јавно здравје на Р Северна Македонија = Institute of Public Health of R North Macedonia, 2020)
Twin pregnancies are high-risk pregnancies accompanied with multiple complications, such as: spontaneous abortion, preterm rupture of the membranes, preterm delivery, intrauterine death of one or both twins etc. There is no consensus about the management of twin pregnancies complicated with preterm rupture of the membranes of one twin and risk of preterm delivery. These cases are rarely found in the literature. We present a case of a 35 years old patient, hospitalized in a tertiary level institution, because of a diamniotic dichorionic twin pregnancy complicated with preterm rupture of the membranes of the first twin at 19 weeks of gestation. She had one delivery with Caesarean section 16 years ago. In consultation with the patient induction of labor was done with delivery of the first twin, a death male fetus. After that, antibiotics and tocolytic therapy were administrated and the patient remained in the hospital about one week. The patient was discharged at home with regular control of her condition and condition of the fetus. The patient was again hospitalized at 33 weeks of gestation with uterine contractions on cardiotocography. After administration of corticosteroid therapy for fetal lung maturation she delivered spontaneously the second twin in a good condition and she was discharged from hospital after 16 days. In twin pregnancies clinicians must think about delayed interval delivery of the second twin, after delivery of the first twin, with an aim to increase chances for survival, especially for pregnancies less than 30 weeks of gestation.
УСПЕШНО ОДЛОЖУВАЊЕ НА ПОРОДУВАЊЕТО НА ВТОРИОТ БЛИЗНАК ПО РАНА РУПТУРА НА ПЛОДОВИТЕ ОБВИВКИ КАЈ ПРВИОТ БЛИЗНАК: ПРИКАЗ НА СЛУЧАЈ
Keywords: preterm delivery; preterm premature rupture of the membranes; twin pregnancy